Three‐dimensional reconstruction of black tiger prawn (Penaeus monodon) spermatozoa using serial block‐face scanning electron microscopy. (14th February 2016) - Feng, Tianyi; Paterson, Brian D.; Webb, Robyn; Johnston, Stephen D.
ABSTRACT: Serial Block‐Face Scanning Electron Microscopy (SBF‐SEM) was used in this study to examine the ultrastructural morphology of Penaeus monodon spermatozoa. SBF‐SEM provided a large dataset of sequential electron‐microscopic‐level images that facilitated comprehensive ultrastructural observations and three‐dimensional reconstructions of the sperm cell. Reconstruction divulged a nuclear region of the spermatophoral spermatozoon filled with decondensed chromatin but with two apparent levels of packaging density. In addition, the nuclear region contained, not only numerous filamentous chromatin elements with dense microregions, but also large centrally gathered granular masses. Analysis of the sperm cytoplasm revealed the presence of degenerated mitochondria and membrane‐less dense granules. A large electron‐lucent vesicle and "arch‐like" structures were apparent in the subacrosomal area, and an acrosomal core was found in the acrosomal vesicle. The spermatozoal spike arose from the inner membrane of the acrosomal vesicle, which was slightly bulbous in the middle region of the acrosomal vesicle, but then extended distally into a broad dense plate and to a sharp point proximally. This study has demonstrated that SBF‐SEM is a powerful technique for the 3D ultrastructural reconstruction of prawn spermatozoa, that will no doubt be informative for further studies of sperm assessment, reproductive pathology and the spermiocladistics of penaeid prawns, and other decapod crustaceans. J. Morphol. 277:565–574, 2016. © 2016 Wiley Periodicals, Inc.